Molecular diagnostics of rare inherited SYNDROMES with a view on diagnostic test development - Pohjola, Pia (Annales Universitatis Turkuensis D 1024, 2012)
CHARGE syndrome, Sotos syndrome and 3p deletion syndrome are examples of rare inherited syndromes that have been recognized for decades but for which the molecular diagnostics only have been made possible by recent advances in genomic research. Despite these advances, development of diagnostic tests for rare syndromes has been hindered by diagnostic laboratories having limited funds for test development, and their prioritization of tests for which a (relatively) high demand can be expected. In this study, the molecular diagnostic tests for CHARGE syndrome and Sotos syndrome were developed, resulting in their successful translation into routine diagnostic testing in the laboratory of Medical Genetics (UTUlab). In the CHARGE syndrome group, mutation was identified in 40.5% of the patients and in the Sotos syndrome group, in 34%, reflecting the use of the tests in routine diagnostics in differential diagnostics. In CHARGE syndrome, the low prevalence of structural aberrations was also confirmed. In 3p deletion syndrome, it was shown that small terminal deletions are not causative for the syndrome, and that testing with arraybased analysis provides a reliable estimate of the deletion size but benign copy number variants complicate result interpretation. During the development of the tests, it was discovered that finding an optimal molecular diagnostic strategy for a given syndrome is always a compromise between the sensitivity, specificity and feasibility of applying a new method. In addition, the clinical utility of the test should be considered prior to test development: sometimes a test performing well in a laboratory has limited utility for the patient, whereas a test performing poorly in the laboratory may have a great impact on the patient and their family. At present, the development of next generation sequencing methods is changing the concept of molecular diagnostics of rare diseases from single tests towards whole-genome analysis.